Conservative treatment of ameloblastoma: A systematic review (Research, Society and Development, 2023)
Ameloblastomas are benign odontogenic tumors, yet they exhibit locally aggressive behavior and a high recurrence rate, originating from cells responsible for enamel formation during development. Due to such behavior, the clinical management and treatment of this lesion are widely discussed regarding conservative or radical approaches. This study aimed to provide evidence-based data on the choice of treatment for ameloblastoma, as well as the benefits and drawbacks of conservative treatment. The objective of this study was to furnish evidence-based information regarding the selection of treatment for ameloblastoma, including an evaluation of the advantages and disadvantages of conservative therapy. The research was executed in accordance with rigorous procedures of a systematic literature review, exclusively encompassing primary research studies. These investigations encompassed articles listed in the SciELO, BVS, and PubMed databases spanning from 2013 to 2023. Initially, 83 articles were identified, from which 25 satisfied the eligibility criteria. This investigation has discerned that the choice of treatment strategy will be contingent upon the ameloblastoma type, patient's age, lesion dimensions, aesthetic and functional impairments, and patient compliance with the chosen treatment modality. The conservative approach exhibited superior outcomes among younger patients.